Evaluating resistant brassica trap crops to manage Heterodera schachtii (Schmidt) infestations in Eastern England - Wright, Alistair J.D.; Back, Matthew A.; Stevens, Mark; Sparkes, Debbie L. (Wiley, 2019)
BACKGROUND: The beet cyst nematode (BCN), Heterodera schachtii Schmidt, is a plant parasitic nematode which causes severe losses to yields of sugar beet. Resistant brassicas (radish and mustard) have been bred to be planted after the harvest of a main crop, such as a cereal, and encourage hatch of BCN juveniles. The resistant plants stimulate hatch of the juveniles but are not suitable hosts. Juveniles are unable to complete their lifecycle and thus populations are lowered. This research aimed to investigate the effectiveness of a range of these brassicas in terms of BCN control when grown in infested fields in Eastern England. RESULTS: Experiments were sown using four different radish cultivars, which differed in their resistance to BCN, and one resistant mustard variety. Field experiments were sown in early September in 2016 and 2017.Significant reductions in BCN populations were only found following the resistant mustard and the radish with the greatest resistance level. CONCLUSIONS: Further research is needed to understand how best to utilise the brassica s and whether they are economically viable when alternative management options for BCN are available. Time of planting may be crucial to fully achieve their BCN reducing potential.